1978
DOI: 10.1136/adc.53.9.726
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural heart disease in the newborn. Observations during one year in a perinatal service.

Abstract: SUMMARY One-third of 327 newborn infants referred to the perinatal service of the Hospital for Sick Children during 1975 with suspected cardiopulmonary disorders proved to have nonstructural heart disease. Most of these were term infants with transient tachypnoea or cyanosis who recovered. A history of fetal distress or difficult delivery was commonly associated. The haemodynamic disorder for most was a delay in the normal progress of the transitional circulation. Evidence of myocardial ischaemia was present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The occurrence of myocardial ischemia and infarction in newborns without "structural" heart disease and with normal coronary arteries has received renewed attention in the literature in recent years [2,25,26] . Pathologists have shown that widespread myocardial necrosis occurs in infants subjected to birth asphyxia and a variety of hypoxic stresses [2,7,10,15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of myocardial ischemia and infarction in newborns without "structural" heart disease and with normal coronary arteries has received renewed attention in the literature in recent years [2,25,26] . Pathologists have shown that widespread myocardial necrosis occurs in infants subjected to birth asphyxia and a variety of hypoxic stresses [2,7,10,15] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that this is because the volume overload on the heart is obligatory ; that is, the volume load continues despite increase in pulmonary artery resistance [29] . Myocardial ischemia and infarction sometimes complicate congenital heart anomalies Pediatric Cardiology [12,19] and may also occur in the otherwise structurally normal heart [2,15,[25][26][27] in response to neonatal stress . We investigated the possibility that myocardial ischemia and infarction may be partly responsible for the severe failure in the infant with CAVM .…”
mentioning
confidence: 99%
“…If the cardiovascular system is damaged the fetus is compromised. In recent years interest in the myocardial function and reserve in perinatal hypoxia or asphyxia has been growing, and there is abundant evidence that in many instances the myocardium is affected in states of severe hypoxia (Burnard and James, 1961;Rowe and Hoffman, 1972;Rowe et al, 1978). While this may reflect direct myocardial damage in hypoxia (de Sa, 1977), the possibility that damage to the coronary arterial tree may be an important factor does-not appear to have been considered, and the earlier observations of Gruenwald (1949) have passed unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…A second group of neonates with nonstructural heart disease are reported separately (Rowe et al, 1978). Table 1 summarises the final diagnoses in the neonates with structural congenital heart disease.…”
Section: Methodsmentioning
confidence: 99%